(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The current in vivo study is done to compare the retention, marginal staining, marginal integrity, and development of new carious lesions between a hydrophilic resin-based sealant and a giomer-based pit and fissure sealant on primary molars.Study Design:180 primary molars from 45 participants are taken into consideration in this randomised clinical investigation. 90 primary molars were sealed with Beautisealant (Group 1) and the other 90 primary molars were sealed with Embrace Wet Bond sealant (Group 2). To evaluate the clinical performance Modified USPHS criteria will be used and applied immediately following sealant application, at 3, 6, and 12 months. The entire set of data was gathered, enteredinto MS Excel, and examined with SPSS 16.0. The parameters of clinical evaluation were compared using the Fisher's exact test and the Pearson Chi-Square test.Result: At the end of 12 months, 75.9% of group 2 primary molars still had sealants in place, compared to 26.2 percent of group 1, which is statistically significant (p.001). Conclusion: Hydrophilic sealants may be employed as efficient fissure sealants, particularly in children who are at high risk for tooth decay, overly salivate, are physically and intellectually challenged, have partially erupted molars, and for children enrolled in community care programs.